2014
DOI: 10.7314/apjcp.2014.15.10.4319
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase C Epsilon 1 (PLCE1 rs2274223A>G, rs3765524C>T and rs7922612C>T) Polymorphisms and Esophageal Cancer Risk in the Kashmir Valley

Abstract: Background: Phospholipase C epsilon 1 (PLCE1) encodes a member of the phospholipase family of proteins that play crucial roles in carcinogenesis and progression of several cancers including esophageal cancer (EC). In two large scale genome-wide association studies (GWAS) single nucleotide polymorphisms (SNP, rs2274223A>G, rs3765524C>T) in PLCE1 were identified as novel susceptibility loci of esophageal cancer (EC) in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…At present, esophageal cancer ranks the 8th of the incidence of malignant tumors all over the world and patients with esophageal cancer in China takes up more than 50% of the world, with the mobility and cancer related mortality ranking the 4th, highly occurring in Lin County and Anyang City, Hennan Province (Yuan et al, 2014;Malik et al, 2014;Yang et al, 2014;Somi et al, 2014;Zheng et al, 2014). About 50% of patients were found with the advanced period of esophageal cancer when diagnosed, with unfavorable prognosis, about 6~8 months of natural course, 5%~7% five-year survival rate (; Liu et al, 2014;Mai et al, 2014;Zhao et al, 2014;Jiang et al, 2014;Wang et al, 2014;Stefani et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…At present, esophageal cancer ranks the 8th of the incidence of malignant tumors all over the world and patients with esophageal cancer in China takes up more than 50% of the world, with the mobility and cancer related mortality ranking the 4th, highly occurring in Lin County and Anyang City, Hennan Province (Yuan et al, 2014;Malik et al, 2014;Yang et al, 2014;Somi et al, 2014;Zheng et al, 2014). About 50% of patients were found with the advanced period of esophageal cancer when diagnosed, with unfavorable prognosis, about 6~8 months of natural course, 5%~7% five-year survival rate (; Liu et al, 2014;Mai et al, 2014;Zhao et al, 2014;Jiang et al, 2014;Wang et al, 2014;Stefani et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This phospholipase has been reportedly associated with intracellular signaling through the regulation of a variety of proteins, such as the protein kinase C (PKC) isozymes and the proto-oncogene ras (Rhee, 2001;Bunney et al, 2009). Also replicated independent studies have validated the association of PLCE1 polymorphism with esophageal cancer in Chinese Kazakh and Kashmiri population Malik et al, 2014). Recent studies have shown that, increased PLCE1 expression is related to the development of bladder cancer (Ou et al, 2010).…”
Section: Introductionmentioning
confidence: 94%
“…A genome-wide association pathway analysis found that rs3765524 contributed to GC susceptibility [81, 82], while a case-control study of the Chinese population showed that rs3765524 was associated with disease risk in GC and ESCC [58, 67, 83]. Investigations of South Asian patients showed similar results for GC [72] but not for ESCC [78, 84]. Additionally, a recent meta-analysis showed that like rs2274223, rs3765524 was significantly associated with disease risk [79].…”
Section: Discussionmentioning
confidence: 99%